Analysis Of The Cancellation Of Ownership Certificates Without Official Notice (Case Study Of The Cibinong Court Decision No.99/Pdt.G/2016/PN Cbi) - Desya Lusiarni Purba (Semarang State University Undergraduate Law and Society Review, 2025)
This study examines the legal implications of canceling a Certificate of Ownership (SHM) without officially notifying the certificate holder, using Cibinong District Court Decision No. 99/Pdt.G/2016/PN Cbi as a case study. The research aims to assess how well the cancellation process aligns with the relevant laws and regulations, especially the Basic Agrarian Law (UUPA) and ATR/BPN Regulation No. 21 of 2020. The research employs a qualitative method with a normative legal approach, involving the examination of pertinent legal documents and regulations. The results show that the Land Office's one-sided annulment of the SHM, carried out without the involvement or notification of the rightful holder, violates due process and legal certainty principles. This action contravenes Article 32 of the ATR/BPN Regulation No. 21/2020, which stipulates that legal products cannot be annulled if the rights holder is not involved in the case and has obtained their rights in good faith. This study concludes that cancelling land certificates without involving the right holders ignores legal protection, creates legal uncertainty and has the potential to cause injustice.  In terms of land rights protection, it is recommended that the principles of transparency, fairness and the rule of law become the basis for future dispute resolution.